Analysis of the Influence of Education Level and Competency on Organizational Commitment through Work Motivation in the Garment Sub-Sector in Serang Regency - Juariah, Siti; Nuryanto, Uli Wildan; Handayani, Yolla Sukma (Universitas Lampung, 2024)
This study examines the influence of education level and competency on work motivation and organizational commitment among garment company employees in Serang Regency. Specifically, it analyzes the direct effects of education level and competency on work motivation and organizational commitment, as well as the indirect effects of education level and competency on organizational commitment through work motivation. This research employs a quantitative approach with a correlational design, involving a total population of 850 employees. The sample size of 190 respondents was determined using a proportional sampling technique, multiplying the number of indicators by the Likert scale. Data analysis was conducted using regression analysis with the SmartPLS statistical tool. The findings reveal that out of seven tested hypotheses, four were accepted, and three were rejected. The results indicate that education level significantly influences both work motivation and organizational commitment, while competency does not significantly affect either work motivation or organizational commitment. Additionally, education level has a significant impact on organizational commitment through work motivation, whereas competency does not exhibit such an effect. Overall, this research highlights the critical role of education level and motivation in enhancing organizational commitment, while competency does not contribute significantly in this context.Keywords: Education Level, Competency, Garment Industry, Organizational Commitment, Quantitative Research, Structural Equation Modeling (SEM), Work Motivation